The Study of Dialects in Uzbek Linguistics in the Period of Independence - Mamatismoilova Hanifa (Zien Journals, 2023)
This article discusses the contribution of Uzbek dialectologists to the collection and study of materials on Uzbek dialects, which laid the foundation for the emergence and development of an independent scientific direction - Uzbek dialectology. It is known that the diversity of the Uzbek language and their diversity distinguishes this language from other Turkic languages. This is fully confirmed by scientific research conducted in the field of Uzbek dialectology, the historical and linguistic evidence contained in it. At the same time, there are issues related to the dialects of the indigenous population of the region
Keywords: historical and etymological; Alisher Navoi; Abulgazi Bakhodirkhan